Covid-19 Maneuver on Socio-economic: Exploitation Using Correlation - Juliansyah Roy; Zamruddin Hasid; Diana Lestari; Dio Caisar Darma; Erwin Kurniawan A (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
Apart from the health aspect, Covid-19 has also had socio-economic effects from the fragile balance of development that has designed so far. Instantly, humans experience suffering that is difficult to predict when it will stop. The primary aim of this study is to evaluate the fragility of the socio-economic order because of Covid-19. These two motifs are the basic essence of human beings, especially the population in Indonesia. A two-way correlation applied to the IBM SPSS to predict the effect of Covid-19 on poverty, natality, minimum wages, divorce, GRDP per capita, unemployment, and crime over two periods. The database is as cross-section covering ten areas in East Kalimantan Province. We found the importance of the correlation parameter in this study that it turns out that Covid-19 closely related to the minimum wage, unemployment, and crime. Because Covid-19 has a positive effect on these three variables and the probability has met the criteria, this is also the right instrument for the government in determining special strategies. The implications of the research are to contribute to long-term management in disaster mitigation planning.